Strengthening the Understanding of Business Administration Students Regarding the Marketing Management Process in Businesses - Yusi Irensi Seppa; Maya Kasmita; Andi Muhammad Rivai; Aris Baharuddin; Siti Syarifah Wafiqah Wardah (PT. Global Research Collaboration, 2024)
In planning and implementing marketing management, the marketing environment and marketing management process need to be considered. This Community Service aims to provide strengthening of UNM Business Administration students' understanding of the marketing management process at PT. Victoria Care Indonesia Tbk. This community service activity focuses on the material of the marketing management process. The method of delivering information used is by providing reinforcement of students' understanding through theory and practice/direct visits to the company. From the results of the observations made, the results of the most optimal marketing management process at PT. Victoria Care Indonesia Tbk in Bali are designing marketing strategies. The results of this community service activity are that they can improve the skills that will be needed when entering the workforce, can understand the marketing management process in a company to be able to increase sales of its products. can develop new ideas and innovations and can have a competitive advantage to realize the character of students who have an entrepreneurial spirit for the interests and goals of the Business Administration study program, Faculty of Social Sciences, UNM.